Produtividade e valor nutritivo de pastagens tendo como base o capim- elefante em sistemas de produção com baixo uso de insumos - Arrial, Mariani (2022)
Elephant grass has high forage potential and adaptation capacity in tropical and subtropical regions. It is usually grown intensively and fertilized with high doses of mineral fertilizers. This strategy results in high production costs and environmental impacts. The objective of this study was to evaluate different grazing systems with elephant grass in organic and conventional production systems that use of low amounts of inputs. The treatments consisted of four grazing systems: (i) one in organic production, in a polyculture, and in association with other spontaneous growth grasses and three in conventional production, (ii) in a monoculture; (iii) in a polyculture, in association with other grasses; and (iv) in association with other grasses + pinto peanut. In all the polyculture systems, elephant grass was planted in rows, and between the rows, annual ryegrass was introduced. The uniform criterion among the grazing systems was the level of nitrogen fertilization (120 kg of N/ha per year). Forage samples were collected before and after grazing to evaluate plant and animal responses. In the grazing system in organic production, there was a better distribution of forage between the periods of the year. In comparison to the other systems, the conventional production system with a monoculture of elephant grass had a higher forage production, with an irregular distribution during the year. In comparison to in the polyculture system without legume, in the system with grass-legume, there was higher forage production, with better nutritional value.